Analysis Determinants of Unwanted Pregnancy in Adolescents : Literature Review - Dwi Ristanti, Adenia; Wijayanti, Wijayanti; Wulandari, Retno (Universitas Kusuma Husada Surakarta, 2024)
Background: Pregnancy in teenagers beginning from pregnancy no desired, is one phenomenon recent social. This the more increase occurs in the environment public give rise to its height possible abortion triggering an increase in the MMR Evidence search strategy: this research is a literature review research using the ScienceDirect, PUBMED, BMC, and Google Scholar databases with keywords _